Bioactive compounds from extremophiles : genomic studies, biosynthetic gene clusters, and new dereplication methods /: genomic studies, biosynthetic gene clusters, and new dereplication methods. (2015) - Giddings, Lesley-Ann; Newman, David J, 1939-
No abstract available